Tiddas Showin' Up, Talkin' Up and Puttin' Up : Indigenous Women and Educational Leadership : Final Project Report. - Bunda, Tracey A.; White, Nereda (Australian Learning and Teaching Council (ALTC), 2009)
Final report from a project concerned with Indigenous women and educational leadership. The naming of the project as Tiddas Showin' Up, Talkin' Up and Puttin' Up draws from two Indigenous sources. The first reinscribes the white way of knowing the familial relationship of 'sister' in the Indigenous generic language term of 'tidda'; the second, Showin' Up, 'Talkin' Up' and Puttin' Up, calls into agentic being the constructions of our leadership as Indigenous women, grounded in their communities for particular reference to leadership in the university. Indigenous higher education networks were utilised to recruit Indigenous women located in universities throughout the nation. The approach to the project comprised four workshops conducted at the end of each semester in 2007 and 2008. Each workshop addressed a specific theme: learning and teaching; scholarship; university administration and management; and community engagement. The approach also included the development of a website profiling the women engaged in the project. The project promoted and supported strategic change in higher education by strengthening the participation and leadership capacity of Indigenous women academics. It has begun to effect long-term systemic change and by ripple effect, strengthened and contributed to leadership capacity of Indigenous women within Indigenous communities, and also within broader Australian society.